Terahertz Microstrip Patch Antenna for Breast Tumour Detection - Md Azani, Muhamad Afif Syahiddin; Zainal Abidin, Zuhairiah (Journal of Electronic Voltage and Application, 2023)
Breast cancer is one of the most common cancers among Malaysian women. It is critical to discover strategies to detect the tumour early on. Terahertz (THz) frequency provides excellent qualities for detecting tumours such as low photon energy and non-ionising radiation as compared to prior methods such as mammography, ultrasound, and magnetic resonance imaging (MRI) that use optical to X-ray frequencies. The purpose of this work is to analyse and locate a breast tumour as well as to compute the maximum specific absorption rate (SAR) value. It was designed a THz rectangular microstrip patch antenna with an inset feed. To improve the antenna's performance, graphene was used for the patch and polyimide for the substrate. This antenna covered a bandwidth of 31.6 GHz and worked in the frequency range of 0.283-0.599 THz. To identify the location of a tumour, compute the SAR value, and localise the tumour, SAR simulation was used. The maximum SAR shifted to the tumor's position due to greater absorption rate around its tissue due to higher dielectric constant features. It was calculated that 1e-05g of average mass is required to be less than total tissue mass, which is 2.0063e-05g. SAR study revealed a maximum SAR value of 2.49391e+06 W/kg, which was not more than the overall absorption rate for human body safety. The SAR calculation result revealed that the tumour is within the range of the tumor's initial location.